Mechanism of Action of a Peroxisome Proliferator-Activated Receptor (PPAR)-δ Agonist on Lipoprotein Metabolism in Dyslipidemic Subjects with Central Obesity - Ooi, Esther M. M.; Watts, Gerald F.; Sprecher, Dennis L.; Chan, Dick C.; Barrett, P. Hugh R. (The journal of clinical endocrinology and metabolism, 2011)
Context:Dyslipidemia increases the risk of cardiovascular disease in obesity. Peroxisome proliferator-activated receptor (PPAR)-δ agonists decrease plasma triglycerides and increase high-density lipoprotein (HDL)-cholesterol in humans.Objective:The aim of the study was to examine the effect of GW501516, a PPAR-δ agonist, on lipoprotein metabolism.Design, Setting, and Intervention:We conducted a randomized, double-blind, crossover trial of 6-wk intervention periods with placebo or GW501516 (2.5 mg/d), with 2-wk placebo washout between treatment periods.Participants:We recruited 13 dyslipidemic men with central obesity from the general community.Main Outcome Measures:We measured the kinetics of very low-density lipoprotein (VLDL)-, intermediate-density lipoprotein-, and low-density lipoprotein (LDL)-apolipoprotein (apo) B-100, plasma apoC-III, and high-density lipoprotein (HDL) particles (LpA-I and LpA-I:A-II).Results:GW501516 decreased plasma triglycerides, fatty acid, apoB-100, and apoB-48 concentrations. GW501516 decreased the concentrations of VLDL-apoB by increasing its fractional catabolism and of apoC-III by decreasing its production rate (P < 0.05). GW501516 reduced VLDL-to-LDL conversion and LDL-apoB production. GW501516 increased HDL-cholesterol, apoA-II, and LpA-I:A-II concentrations by increasing apoA-II and LpA-I:A-II production (P < 0.05). GW501516 decreased cholesteryl ester transfer protein activity, and this was paralleled by falls in the triglyceride content of VLDL, LDL, and HDL and the cholesterol content of VLDL and LDL.Conclusions:GW501516 increased the hepatic removal of VLDL particles, which might have resulted from decreased apoC-III concentration. GW501516 increased apoA-II production, resulting in an increased concentration of LpA-I:A-II particles. This study elucidates the mechanism of action of this PPAR-δ agonist on lipoprotein metabolism and supports its potential use in treating dyslipidemia in obesity.